Kunstenaarsgids Troop II Artists Guide. - Anthuenis, Daan; Augustijns, Mon; Bambust, Dimitri; Bossuyt, Martine; v.d. Burcht, A.; Van Den Bussche, Willy; Claessens, Bieke; De Gezelle, Dirk; De Roy, Paul; De Vos, Johan; Van De Winkel, Dorothea; Dix, John; et al. (St. Niklaas : VZW & Galerij Seven Arts, 1998)
Allaerts, Raymond ; Balboa, Frank ; Beckx, Hilde ; César ; Cassiman, Jacques ; Cassiman, Roland ; De Belder, Inge ; De Boey, Leo ; De Cuyper, Jean Pierre ; De Geyter, Geert ; D'Heedene, Stefaan ; D.D. Trans ; Depoorter, Eva ; De Roy, Paul ; De Vuyst, Allan ; Dix, John ; Florin, Jan ; Foltin, Bruno ; Francot, Magda ; Handsaeme, Hilde ; Hannes, Tom ; Hantson, Peter ; Hufkens, Marc ; Jaspers, Liza ; Jonnaert, thierry ; Lapere, Luc ; Neetens, Raymond Minnen Beatrice ; Nupie, Roger ; Oosterlinck, Guido ; Pause, Monique-Jeanne ; Pee, Peter ; Peerlings, Frans ; Pieterman, Johanna ; Rochus-Kraus, Joseé ; Savels, Daniël ; Schellinck, Diane ; Standaert, Dora ; de Perre, Gerda Van ; Vandermarliere, Kaat ; de Vijver, Theo Van ; De Winkel, Dorothea Van ; Van Durme, Jeanine ; Van Eeckhout, Willy ; Van Engeland, Hennie ; Arena, Guy Van Hoof / ; Vanoppen, Viviane ; Van Waes, Mona ; Wolters, Hans ; Wouters, Patty ; Bossuyt, Francis Aerts Martine ; Cash, Robert ; Ceusters, Paula ; Claessens, Bieke ; Dheere, Christine ; Fierens, Luce ; Fooy, Hans ; Haenen, Toon ; Jorissen, Ann ; Kuyken, Rita ; Ramon, Carine ; Stallaert, Hilde ; Vanlerberghe, Francine ; Van Sebroeck, Annina ; Van Wauwe, Leona ; Verhaeghe, Marjan ; Verstraete, Nico
Biografie
Nederlands & Frans & Engels
boek
Keywords: België